Firecracker injuries during Diwali festival: The epidemiology and impact of legislation in Delhi - Tandon, R.; Agrawal, K.; Narayan, R.P.; Tiwari, V.K.; Prakash, V.; Kumar, S.; Sharma, S. (Indian Journal of Plastic Surgery, 2012)
Setting and Design: A hospital-based retrospective study of firecracker-related injuries was carried out at a government sponsored hospital in Delhi. Materials and Methods: 1373 patients attended the emergency burn care out-patients clinic during 2002-2010 pre-Diwali, Diwali and post-Diwali days. Every year, a disaster management protocol is revoked during these 3 days under the direct supervision of the Ministry of Health and Family Welfare, Government of India. Results: There was an increase in the number of patients of firecracker-related injuries in Delhi national capital region from the year 2002 to 2010, based on the hospital statistics. During the study period, the hospital received approximately one patient with firecracker-related injury per 100,000 population of the city. 73.02% of the victims were 5-30 years old. Majority (90.87%) of them sustained <5% total body surface area burn. Conclusions: In spite of legislations and court orders, the number of patients is on the rise. The implementation agencies have to analyse the situation to find a way to control this preventable manmade accident. Websites, emails, SMS, social sites, etc. should be used for public education, apart from conventional methods of public awareness.
Keywords: Disaster; Diwali; firecracker; legislation; noise pollution